2014
DOI: 10.1155/2014/483657
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Reovirus with Autophagy

Abstract: Autophagy participates in multiple fundamental physiological processes, including survival, differentiation, development, and cellular homeostasis. It eliminates cytoplasmic protein aggregates and damaged organelles by triggering a series of events: sequestering the protein substrates into double-membrane vesicles, fusing the vesicles with lysosomes, and then degrading the autophagic contents. This degradation pathway is also involved in various disorders, for instance, cancers and infectious diseases. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…These genes work in coordination to regulate autophagy, including the formation of autophagosomes and their fusion with lysosomes [ 10 ]. Under normal conditions, autophagy proceeds at a basal level, but it is markedly activated in response to a variety of extracellular and intracellular stimuli, including nutrient starvation, energy depletion, reactive oxygen stress and microbial infection [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes work in coordination to regulate autophagy, including the formation of autophagosomes and their fusion with lysosomes [ 10 ]. Under normal conditions, autophagy proceeds at a basal level, but it is markedly activated in response to a variety of extracellular and intracellular stimuli, including nutrient starvation, energy depletion, reactive oxygen stress and microbial infection [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding BTV, we speculate that autophagy is likely to be involved in BTV infection based on several experimental clues: (i) In one study, activated host autophagy appeared to inhibit post-BTV infection when cells were treated with two compound agents, C003 and C052 [ 19 ], but a more specialized and systematic verification has not been reported. In addition, another member of the Orbivirus genus, epizootic hemorrhagic disease virus (EHDV), can induce autophagy in cultured mammalian cells [ 20 ]; (ii) Recent research findings have described the modulation of autophagy by mammalian reovirus (MRV) and by avian reovirus (ARV), which both belong to the Reoviridae family and share a similar virus structure [ 13 , 21 , 22 ]; (iii) Finally, crosstalk has been observed between apoptosis and autophagy pathways [ 23 , 24 ]. Exploitation of the host apoptosis pathway is a critical strategy utilized by BTV for its pathological effects, as evidenced by a recent experimental system that demonstrated that BTV infection triggers apoptosis in mammalian cells and that the uncoating of BTV was required for this process [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…When these cells were pretreated with the autophagy inhibitor 3-methyladenine (3-MA), a fourfold reduction in autophagy was detected at 48 h post reovirus infection [ 57 , 58 ]. Studies involving avian reovirus (ARV) have [ 59 ] into this process. In vitro infection of Vero cells with ARV has shown to induce autophagy via the PI3K/ Akt/mammalian target of rapamycin (mTOR) signaling pathway evidenced by immunoblotting [ 60 ].…”
Section: Mechanisms Of Reovirus-mediated Cell Deathmentioning
confidence: 99%
“…A fourfold reduction in autophagy by 48 h of reovirus infection was demonstrated when RPMI 8226 cells were pre-treated with the autophagy inhibitor 3-methyladenine (3-MA) ( 64 ). Understanding of the mechanisms behind mammalian reovirus-induced autophagy is limited to the above studies; however, in vitro studies involving avian reovirus (ARV) have provided further insight ( 66 , 67 ). ARV infection of Vero cells in vitro induced autophagy via PI3K/Akt/mammalian target of rapamycin (mTOR) signaling detected by immunoblotting ( 67 ).…”
Section: Mechanism Of Oncolysismentioning
confidence: 99%